Low-complexity instantaneous GNSS attitude determination with multiple low-cost antennas - Teunissen, Peter; Nadarajah, Nandakumaran; Giorgi, G.; Buist, P. (Institute of Navigation, 2011)
Carrier phase integer ambiguity resolution is the key to fast and high-precision GNSS positioning and attitude determination. It is the process of resolving the unknown cycle ambiguities of the double-differenced carrier phase data as integers. Once this has been done successfully, the carrier phase data will act as very precise pseudo range data, thus making precise positioning and attitude determination possible. In this contribution, we describe and test the affine-constrained GNSS attitude model and compare its ambiguity resolution performance with that of MC-LAMBDA on a linear array of low-cost receiver/antennas.